Economic Integration in the System of Spatial Development of the Region - T. N. Topoleva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies specific features of economic integration processes in the context of regional market space clustering. Methodological principles of today’s cluster systems are shown and their signs are identified with signs of heterogeneous network associations. The concept of cluster development is investigated in view of the theory of economic complexity in three analytical sections: production agglomerations, innovation ecosystems and cluster initiatives. Transaction nature of innovation character of cluster systems was revealed. The dependence was grounded of innovative cluster opportunities on synergy effects arising as a result of collaboration of participants’ interaction on principles of triple spiral (business, state, science and education field). The author found the objective necessity of raising the level of developing the network interaction in order to avoid the formal approach to cluster functioning. The author puts forward the model of economic clusterization in conditions of innovation economy. The regional economic system is structured with regard to cluster presence, functioning of the network mechanism of coordination activity and symbiosis of hierarchical and market system components. Key types of state cluster policy and important trends in cluster support, which includes cluster initiatives, cluster technologies and cluster consulting in priority of strategic management at the regional level. A conclusion was made that clusters were assigned a part of system-forming elements of sustainable development in regional market space.